The Impact of Social Interaction Problems on Students’ participation In English Class - Nonie Agatha Purba; Meikardo Samuel Prayuda; Fiber Yun Almanda Ginting (Sean Institute, 2026)
This study aims to determine the impact of social interaction problems on students’ participation in English class. In this study, there are two main focuses, namely social interaction problems as the influencing factor and students' classroom participation as the affected variable. This study was conducted at SMP Santo Thomas 3 Medan on seventh-grade students in the 2025/2026 Academic Year. The primary subjects of this study were seventh-grade students, and the data were collected through a triangulation of four instruments: student interviews, student questionnaires, classroom observation checklists, and a teacher questionnaire. This study used a qualitative method to capture students' personal experiences, classroom behaviors, and teacher perceptions. The results of the study showed that students’ participation was heavily shaped by four layered barriers: affective-psychological (fear of making mistakes and low confidence), linguistic-communicative (limited vocabulary and pronunciation difficulties), cognitive-comprehension (difficulty understanding lessons), and socio-environmental barriers (fear of being laughed at by peers and direct questioning pressure). However, the findings also revealed that supportive interaction from the teacher such as giving encouragement, feedback, and utilizing small-group discussions successfully functioned as a reducing factor for these barriers. The implementation of supportive, linguistically scaffolded, and non-threatening interaction patterns is one of the solutions to improve students' verbal engagement. Therefore, it can be concluded that social interaction problems significantly influence students' participation, and creating psychological safety alongside collaborative peer dynamics is essential to move students from passive presence to active participation in English learning.